Analysis of Power Transformer Insulation: A Case Study in 150 kV Bantul Substation - Hidayat, Arief Rahman; Jamal, Agus; Chamim, Anna Nur Nazilah; Syahputra, Ramadoni; Jeckson, Jeckson (Universitas Muhammadiyah Yogyakarta, 2019)
Insulation of the transformer is one of the essential components. So that the quality of the resistance in the isolation of the transformer is essential to note the condition, in order to find out the condition of the transformer isolation, several tests must be performed, namely the polarization index, delta tangent, and break down voltage. In this study, all three tests were carried out on Transformer 1 in the 150 kV Bantul substation. Polarization index testing itself is testing the leakage current on the transformer isolation by comparing the test results for 1 minute with the results of the 10-minute drive test. While delta tangent is testing capacitive leakage current in the isolation transformer, and break down voltage is a test of the ability of the breakdown voltage in transformer insulation oil. Based on the results of the analysis, it can be seen that the value of the transformer polarization index in 2016 and 2018, the average value between the windings has been in the rating of 1.25-2.0. As for the delta tangent test results in 2016 and 2018, the value between the capacitive parts is already in the rating of 0.18% -0.36%. For the breakdown voltage test results in 2016 and 2018, the average breakdown voltage value is 43.9 kV/mm - 65.5 kV/mm. From these data, it can be concluded that the transformer isolation conditions in 2016 and 2018 are in good condition, although there was a decline in the transformer isolation conditions in 2016. However, the National Electric Company has made repairs and maintenance of the isolation transformer. This is seen due to an increase in the quality of transformer insulation in 2018. Repair and maintenance of transformer insulation are done to maximize the work system and the life of the transformer.